Challenges in Diagnosing Staphylococcal Scalded Skin Syndrome in Children with Kwashiorkor: A Case Report - Hamdali, Christie; Sirait, Sondang; Rusvita, Adria; Bhakti, Bawono (UI Scholars Hub, 2023)
Staphylococcal scalded skin syndrome (SSSS) is a type of exfoliating skin disease with high incidence in children. This condition can cause serious morbidity and even mortality with certain comorbid diseases such as malnutrition. Malnutrition could mask the diagnosis of SSSS because of its similarity to numerous differential diagnoses. Accuracy of clinical diagnosis is then essential to determine the proper initial management. This case report presents a 6-month-old male baby with staphylococcal scalded skin syndrome and kwashiorkor. The patient presented with complaints of multiple erythematous plaques and widespread vesicular lesions that subsequently ruptured, resulting in erosions. Physical examination revealed edema, coarse hypopigmented hair, multiple erythematous plaques, erosion, along with scales and crusts. Laboratory examination showed leukocytosis. The patient was administered intravenous ampicillin and chloramphenicol, along with wet dressings. The skin lesions showed improvement, but unfortunately, the patient passed away due to septic shock. Differential diagnoses of the skin lesions are also described, along with clinical signs to help differentiate. Proper diagnosis can help decide the correct early management and improve patient prognosis.